Excessive O-GlcNAcylation Causes Heart Failure and Sudden Death. Issue 17 (27th April 2021) - Umapathi, Priya; Mesubi, Olurotimi O.; Banerjee, Partha S.; Abrol, Neha; Wang, Qinchuan; Luczak, Elizabeth D.; Wu, Yuejin; Granger, Jonathan M.; Wei, An-Chi; Reyes Gaido, Oscar E.; Florea, Liliana; Talbot, C. Conover; et al.
Abstract : Background: Heart failure is a leading cause of death worldwide and is associated with the rising prevalence of obesity, hypertension, and diabetes. O -GlcNAcylation (the attachment of O -linked β-N-acetylglucosamine [ O -GlcNAc] moieties to cytoplasmic, nuclear, and mitochondrial proteins) is a posttranslational modification of intracellular proteins and serves as a metabolic rheostat for cellular stress. Total levels of O -GlcNAcylation are determined by nutrient and metabolic flux, in addition to the net activity of 2 enzymes: O -GlcNAc transferase (OGT) and O -GlcNAcase (OGA). Failing myocardium is marked by increased O -GlcNAcylation, but whether excessive O -GlcNAcylation contributes to cardiomyopathy and heart failure is unknown. Methods: We developed 2 new transgenic mouse models with myocardial overexpression of OGT and OGA to control O -GlcNAcylation independent of pathologic stress. Results: We found that OGT transgenic hearts showed increased O -GlcNAcylation and developed severe dilated cardiomyopathy, ventricular arrhythmias, and premature death. In contrast, OGA transgenic hearts had lower O -GlcNAcylation but identical cardiac function to wild-type littermate controls. OGA transgenic hearts were resistant to pathologic stress induced by pressure overload with attenuated myocardial O -GlcNAcylation levels after stress and decreased pathologic hypertrophy compared with wild-type controls. Interbreeding OGT with OGA transgenic mice rescued cardiomyopathy and premature death, despite persistent elevation of myocardial OGT. Transcriptomic and functional studies revealed disrupted mitochondrial energetics with impairment of complex I activity in hearts from OGT transgenic mice. Complex I activity was rescued by OGA transgenic interbreeding, suggesting an important role for mitochondrial complex I in O -GlcNAc–mediated cardiac pathology. Conclusions: Our data provide evidence that excessive O -GlcNAcylation causes cardiomyopathy, at least in part, attributable to defective energetics. Enhanced OGA activity is well tolerated and attenuation of O -GlcNAcylation is beneficial against pressure overload–induced pathologic remodeling and heart failure. These findings suggest that attenuation of excessive O -GlcNAcylation may represent a novel therapeutic approach for cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.